Circle Association: A Case Study on Adolescent Insecurity - Isak Surya; David Ming (RIRAI Publisher, 2022)
Association is very important to explore and find identity for teenagers, but the association is also vulnerable to mental threats in the form of insecurity that is troubling the future of teenagers. With this research, it is hoped that it can overcome or at least minimize the impact of youth insecurity due to association, so that the prospective youth of the nation's golden generation can avoid prolonged mental illness. Based on the background of this writing, the research problem formulation is obtained, namely: 1) How much influence does social interaction have on adolescent insecurity? This study was designed with the aim of explaining and answering the questions in the focus of the research above with the emphasis, namely: 1) Knowing the magnitude of the influence of association on the emergence of a sense of insecurity in adolescents. 2) Mention and explain the pattern of causes of insecurity in the association. With this research, researchers can find out in depth about the correlation between association and insecurity in adolescents.